1996
DOI: 10.1038/nsb1296-1034
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the origin DNA-binding domain of SV40 T-antigen

Abstract: The structure of the domain from simian virus 40 (SV40) large T-antigen that binds to the SV40 origin of DNA replication (T-ag-OBD131-260) has been determined by nuclear magnetic resonance spectroscopy. The overall fold, consisting of a central five-stranded antiparallel beta-sheet flanked by two alpha-helices on one side and one alpha-helix and one 3(10)-helix on the other, is a new one. Previous mutational analyses have identified two elements, termed A (approximately 152-155) and B2 (203-207), as essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 24 publications
2
130
0
Order By: Relevance
“…B, domain architecture of SV40 Tag. The DnaJ chaperone domain (72), SV40 OBD (73), and helicase domain (42,43) tution in Tag. Pull-down experiments also showed that K425E, but not K425R, substantially reduced Tag 357-627 binding to p68 1-107 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…B, domain architecture of SV40 Tag. The DnaJ chaperone domain (72), SV40 OBD (73), and helicase domain (42,43) tution in Tag. Pull-down experiments also showed that K425E, but not K425R, substantially reduced Tag 357-627 binding to p68 1-107 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intramolecular Contacts between Domains I and II-The available atomic structures and electron microscopic data on native Tag and its oligomeric forms do not provide information on the location of domain I (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). By immunoprecipitating a native tryptic digest of Tag monomers using a monoclonal antibody against an epitope in domain IIb (Pab204), short fragments containing only domain I were detected in the precipitate, implying that the short domain I fragments remained associated with domain II after digestion.…”
Section: Discussionmentioning
confidence: 99%
“…7A. We subdivided domain II into two parts (a and b) based on a Pronase E-resistant fragment generated with origin DNA-bound Tag (30) and the atomic structure of residues 131-259 (21). Monomeric Tag contains an extremely protease-sensitive region in the C-terminal part of domain IIb (darker shading in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Following the melting event, both proteins function as doubly hexameric helicases (Bullock 1997;Simmons 2000). Unexpectedly, structural studies have revealed that the site-specific DNA-binding domains of BPV E1 and T-antigen possess the same fold, despite sharing <10% amino acid sequence identity (Luo et al 1996;Enemark et al 2000). Li et al (2003) have recently determined the crystal structure of the hexameric T-antigen helicase domain.…”
Section: E1 and The Sv40 Large T-antigenmentioning
confidence: 99%